RANCANG BANGUN SISTEM INFORMASI INVENTARISASI SERAGAM DIGITAL TALENT PADA PT. XYZ BERBASIS WEBSITE - Hesti Rian; Muhamad Danu Cesa (POLITEKNIK LP3I JAKARTA, 2025)
The research conducted revealed obstacles in the data collection and management of uniforms for the Digital Talent program, including: the manual uniform data collection process, and the manual management process, including both Digital Talent participant data collection and uniform distribution. To address these challenges, the author proposes a solution by developing a website-based system that is expected to simplify and expedite the uniform inventory management process, improve service quality, reduce data recording errors, and facilitate inventory data monitoring.